1974
DOI: 10.1029/jb079i026p03981
|View full text |Cite
|
Sign up to set email alerts
|

Xenon isotope anomalies in the carbonaceous chondrite murray

Abstract: Isotopic compositions have been measured mass spectrometrically for xenon fractions released from the carbonaceous chondrite Murray in stepwise heating experiments. The isotopic ratios varied quite considerably; for example, the 136Xe/132Xe ratio in the 1000°C fraction was almost identical to the atmospheric ratio (0.330), whereas the ratio in the 1300°C fraction agreed with that in Sucor (0.305). It appears that these variations can best be explained as being due to the fact that reservoirs of two isotopicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…The experimental procedure employed was essentially the same as that described in previous reports (KURODA et al, 1974KURODA and SHERRILL, 1976), except for the fact that large amounts of rock samples were used for the mass-spectrometric analyses: 7.097 grams of Carney Lake granite; 15.085 grams of Red Rock granite; 15.316 grams of Wausau granite; and 12.374 grams of Westerly granite.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedure employed was essentially the same as that described in previous reports (KURODA et al, 1974KURODA and SHERRILL, 1976), except for the fact that large amounts of rock samples were used for the mass-spectrometric analyses: 7.097 grams of Carney Lake granite; 15.085 grams of Red Rock granite; 15.316 grams of Wausau granite; and 12.374 grams of Westerly granite.…”
Section: Methodsmentioning
confidence: 99%
“…The initial ratio of 26A1 to 27A1 can be cal XENON ISOTOPE ANOMALIES According to KURODA (1971KURODA ( , 1975KURODA ( , 1976KURODA ( , 1979 and KURODA et al (1974KURODA et al ( , 1975, the difference in the isotopic compositions of xenon in the atmosphere and the carbonaceous chon drites can be attributed to a combined effect of (a) mass fractionation, (b) neutron caputre and (c) cosmic-ray irradiation processes which took place in the early solar system. The amount of cosmic-ray-produced 126Xe in car bonaceous chondrites can be calculated from the equations …”
Section: Introductionmentioning
confidence: 99%
“…KURODA et al (1974), on the other hand, have reported that the isotopic composition of the xenon in carbonaceous chondrites can be explained as due to the alterations of the isotopic compositions by a combined effect of a) mass fractionation, b) neutron-capture and c) cosmic-ray. irradiation processes which took place during the early history of the solar system (see also KURODA, 1976).…”
Section: Accordingmentioning
confidence: 99%